Pottery Making Technique in the Early Islamic Era During the Period (1-4 AH / 7-10 AD) Selected Models in the Civilized Museum of Erbil : Technical Analysis Study - Aras Ismail Khider; Mohammed Qadir Ismail (QALAAI ZANIST JOURNAL, 2022)
Pottery is everything made of clay and grilled with fire. As for the word porcelain, they were used for glazed pottery. Pottery is considered one of the most important artistic crafts that man has practiced since prehistoric times and used for his daily needs such as cooking and storing grains, as well as using it for religious rituals and burial of the dead for ease of formation, but in the Islamic era Pottery and pottery are among the most important industries practiced by the Muslim artist since the dawn of Islam. In the beginning, the Arabs followed the same simple traditional methods that were prevalent in the manufacture of pottery and ceramics in Iraq, Egypt and the Levant. However, these al-Fakhrani took the reins in this industry since the second century AH. They began to innovate and innovate, whether in technology, shapes, or decoration. This study deals with technology and pottery in the early Islamic era during the century (1-4 AH / 7-10 AD). Before, in this research, technology and the pottery industry in the early Islamic era were oriented with a scientific study of the types of clay used in the studied models, then we clarified the most important methods used in the studied pottery, then we clarified the most important methods used in surface treatment of pottery and ceramic models, as well as we touched on the most important errors and damage That appeared on some pottery and ceramic models before and after the process of pride, and finally we talked about the types of rims and the general rules of the models studied.